The Influence of the Think Talk Write Cooperative Learning Model on Social Studies Learning Outcomes for Class IV Elementary Schools - Tantri, Tantri Septiarini; Fanny, Arif Mahya (LPPM Universitas Pelita Bangsa, 2024)
This research aims to see the effect of implementing the Think Talk Write (TTW) type cooperative learning model on learning outcomes in the material Benefits of Diversity and Preserving Cultural Diversity for Class IV Elementary School at SDN Gayungan II/423 Surabaya. This research is a quantitative experimental research with a One-Group Pretest-Posttest Design. The data collection technique used was a Pretest-Posttest activity in the form of a multiple choice test. This research used two groups, namely the experimental class and the control class. Class VI-A is an experimental class with 25 students, while class VI-B is a control class with 25 students. The data analysis technique using the T test obtained a Sig (2-tailed) result of 0.000 < 0.05 so that HO was rejected and Ha was accepted, which means it can be concluded that there is an influence of the Think Talk Write (TTW) type cooperative learning model on the learning outcomes of Social Science Class IV Elementary School.